Implementasi Pendidikan Karakter melalui Pengenalan Nilai-Nilai Kearifan Lokal di SDN Burengan 2 Kota Kediri - Karimatus Saidah (Tarbiyatuna Kajian Pendidikan Islam, 2018)
SDN Burengan 2 has a strong commitment in developing the good character of the students. This study aims to analyze related character education implementation through the introduction of local wisdom values that are implemented in SDN Burengan 2 Kediri City. This research uses qualitative approach. Based on the results of the research, it is found that the implementation of character education in SDN Burengan 2 Kediri City has been poured into the vision and mission of the school. For the sake of achieving the vision and mission, the school has carried out various programs that include: obligatory praying, LiSA movement, Friday Javanese program, vegetable eating habits with vegetable protein side dishes every Friday and vegetables with side dish prtein animal every saturday , school counseling services, as well as developing students' potential and talents in the form of extracurricular school activities. Implementation of character education through the introduction of local wisdom is implemented by: applying Javanese language on Friday, learning activities outside the classroom by making visits to educational and cultural places, inspiring class programs, and exploring non-academic potential of students through extracurricular.